1993
DOI: 10.1557/jmr.1993.2380
|View full text |Cite
|
Sign up to set email alerts
|

Interfaces in as-extrudedXDAl/TiC and Al/TiB2metal matrix composites

Abstract: A detailed study was conducted of the microstructure and particle-matrix interfaces in Al/TiCpmetal matrix composites prepared by theXDprocess and subsequent extrusion. A study of the morphology of the TiC particles showed that the surfaces are low index (111) and (200) planes, the former being more common. Direct contact on an atomic scale is established between Al and TiC, allowing chemical bonds to form. Young's modulus is in the range expected for a composite of Al and TiC with good interfacial bonding and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
1

Year Published

1996
1996
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(43 citation statements)
references
References 23 publications
(19 reference statements)
0
40
1
Order By: Relevance
“…The formation of coherent interfaces is difficult, considering the different crystal structures of Al (fcc, a = 0.40496 nm) and TiB 2 (hexagonal, a = 0.3028 nm and c = 0.3223 nm), and the large average size of TiB 2 particles. The observation in this study differs from the semicoherent or special orientation particle-matrix interfaces reported earlier by Mitra et al [27] in the case of the exothermic dispersion (XD) 2024Al-TiB 2 composites with 0.3-lm-size particles inside Al grains, due to the coarser particle size and the location at grain boundaries. Calculations from the weight fraction (considering 5 wt pct) and image analyses have confirmed that the volume fraction of TiB 2 particles is 3. show the optical micrographs of the Al-4.5 (wt pct) alloy and Al-4.5 (wt pct) Cu-5 (wt pct) TiB 2 composites, respectively, subjected to reheating and holding at 632°C for 2 minutes, followed by water quenching.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…The formation of coherent interfaces is difficult, considering the different crystal structures of Al (fcc, a = 0.40496 nm) and TiB 2 (hexagonal, a = 0.3028 nm and c = 0.3223 nm), and the large average size of TiB 2 particles. The observation in this study differs from the semicoherent or special orientation particle-matrix interfaces reported earlier by Mitra et al [27] in the case of the exothermic dispersion (XD) 2024Al-TiB 2 composites with 0.3-lm-size particles inside Al grains, due to the coarser particle size and the location at grain boundaries. Calculations from the weight fraction (considering 5 wt pct) and image analyses have confirmed that the volume fraction of TiB 2 particles is 3. show the optical micrographs of the Al-4.5 (wt pct) alloy and Al-4.5 (wt pct) Cu-5 (wt pct) TiB 2 composites, respectively, subjected to reheating and holding at 632°C for 2 minutes, followed by water quenching.…”
Section: Resultscontrasting
confidence: 99%
“…Again, Figure 11 shows that the average sizes of both the coarse and fine a-Al grains in the pre-hot-rolled composite are smaller, compared to those of the mushy state rolled as-cast composite, but are larger than the average grain size of the quenched samples (Figure 7(b)). In another study [27] Fig. 12-Optical micrographs showing microstructure of the (a) Al-4.5 (wt pct) Cu alloy, subjected to mushy state rolling to thickness reduction of 5 pct at 631°C (30 pct liquid); and Al-4.5Cu-5TiB 2 composite, subjected to mushy state rolling to thickness reduction of (b) 2.5 pct at 632°C (30 pct liquid) and (c) 10 pct reduction at 610°C (10 pct liquid).…”
Section: Mushy State Rollingmentioning
confidence: 92%
“…Generally, interfaces in in situ composites have low energies and are usually semicoherent. [11] This was observed in the HPES-processed NiAl-TiB 2 [13] and NiAl-TiC composites, [12] but not observed in the XD-processed NiAl-TiB 2 composites due to the presence of silicon atoms in the NiAl/TiB 2 interface region. [14] Occasionally, a thin amorphous layer with a thickness of about 3 nm was observed along the TiC/NiAl interface.…”
Section: B Interfacementioning
confidence: 89%
“…This suggests that the interface of the TiC is parallel to the low index and densely packed {100} surface that is one of the low energy surfaces in fcc crystals. [11] Faceting at the interfaces along certain crystallographic directions suggests a tendency to lower interfacial energy. Figure 7 is an HREM micrograph of an interface between NiAl and TiC.…”
Section: B Interfacementioning
confidence: 99%
“…An orientation relationship between (111) Al and (0001) TiB 2 planes was found in a melt-spun Al-5Ti-1B master alloy. [25] Mitra et al [26] and Kostka et al [27] reported semicoherent interface between TiB 2 and Al where no reaction layer or segregation were found. Although these data show the good potential of certain planes of TiB 2 for nucleation of aluminum, the experimental conditions prevailing in these works are far from those of grain refining process.…”
Section: Possible Refining Mechanismmentioning
confidence: 99%